Solar-based irrigation bundle profile and scaling in Ghana - Minh, Thai Thi; Ofosu, Abena (CGIAR Initiative on Mixed Farming Systems, 2022)
There are solutions to sustainable intensification, irrigation technologies, and water management under changing weather and climate conditions; they are just not available to smallholder farmers and vulnerable groups on a large scale. Scaling these solutions, therefore, needs to develop bundles of best-fit solutions to diversify farming and farmer conditions and adapt them to the context of irrigated farming. Throughout the action research process, solar-based irrigation bundle (SBIB) has been scaled in Upper East, Upper West, Northern, Northeast, and Savanah region, Ghana since January 2020. SBIB offers solar-powered irrigation pumps and pay-as-you-go and pay-as-you-own (PAYGO/PAYOWN) financing services to smallholder farmers in combination with tailoring their business models to different client segments (ability to pay, frequency, amount) to lower the barrier for upfront investment cost, enabling solar irrigation adoption and enhancing productivity and income throughout the year. This SBIB profile consists of three components: 1) bundle components and characteristics, 2) assessing the scalability and scaling potential of the bundle, and 3) developing scaling strategies.